Extending Students' Speaking Skills in The Eleventh-Grade by Using Round Robin Technique (R2T) - Yuniarti, Vyna; Anggeriani, Yeni; Saputra, Frian (CV. Doki Course and Training, 2023)
This study was aimed to find out whether or not there was any significant difference in speaking skill between the students’ who were taught by using Round Robin technique and those who were not. There were 60 students of eleventh-grade students of SMA Negeri 7 Prabumulih involved in this study as the sample. They were divided into two groups, experimental and control groups, both groups consisted of 30 students. This study used quasi non-equivalent group design. The experimental group were taught by using Round Robin technique meanwhile the control group were taught by using lecturing method. The result showed that the mean score of experimental groups increased from 70,88 in pre-test to 78,67 in post-test. Furthermore, the result of independent t-test from experimental group and control group shown that the t-obtained was 2,625 and it was higher than t-table 1,9977. It means that there was any significant difference between experimental and control groups which was caused by Round Robin technique given to the experimental group. It can be concluded that there was significant difference between students who were taught using Round Robin technique and students who were not.